Hallux rigidus: evaluation of the postoperative outcomes of cheilectomy combined with modified Lelièvre resection arthroplasty - Azeredo, Mariana Alcântara Roldi de; Maluf Neto, Joaquim (Scientific Journal of the Foot & Ankle, 2019)
Objective: This study evaluated the postoperative outcomes of patients with hallux rigidus who underwent cheilectomy combined with modified Lelièvre resection arthroplasty. Methods: This retrospective cross-sectional study applied the adapted American Orthopedic Foot and Ankle Society (AOFAS) forefoot questionnaire. A total of 28 patients (31 feet with hallux rigidus) were evaluated and treated following the same clinical and surgical protocol between February 2010 and June 2018. We evaluated pain, footwear use, sports activity, surgical complications, and the AOFAS score before and after surgery. Results: All patients who underwent surgery showed improved AOFAS scores and reduced pain with satisfactory functional performance. Conclusions: The use of cheilectomy combined with modified Lelièvre resection arthroplasty was effective, especially with regard to maintaining foot function, significantly improving pain and gait performance, and providing the possibility of wearing ordinary footwear, thereby increasing patient quality of life. This result was consistent with the extant literature on the topic. Level of Evidence IV; Therapeutic Study; Case Series.